Education and social change in Spain: from crisis to opportunity. Issue 2 (3rd May 2016) - Cortés-González, Pablo; Rivas-Flores, J.Ignacio; Leite-Méndez, Analía E.
Abstract : This paper analyses a particular socio-educational experience in a marginalised neighbourhood in Malaga, Spain. This initiative came about as an institutional proposal to combat neoliberal austerity policies and is known as the 'Casa de la Buena Vida'. It aims to generate new educational practices based on solidarity, dignity and justice. The methodology followed entailed carrying out an ethnography at this institution, participating in the initiative over a period of 4 years. At the same time, life histories of some of its most notable members were drawn up. In the results section we offer an analysis of the particular identities that are created as a consequence of the living conditions, social conflicts, multicultural nature and survival strategies that operate in a welfarist policy system. We also analyse this institution's socio-educational proposal using alternative social practices that enable other subjectivities to develop.